2005
DOI: 10.1074/jbc.m414671200
|View full text |Cite
|
Sign up to set email alerts
|

A Novel Caspase-1/Toll-like Receptor 4-independent Pathway of Cell Death Induced by Cytosolic Shigella in Infected Macrophages

Abstract: Shigella-induced macrophage cell death is an important step in the induction of acute inflammatory responses that ultimately lead to bacillary dysentery. Cell death was previously reported to be dependent upon the activation of caspase-1 via interaction with IpaB secreted by intracellular Shigella, but in this study, we show that Shigella infection of macrophages can also induce cell death independent of caspase-1 or IpaB activity. Time-lapse imaging and electron microscopic analyses indicated that caspase-1-d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
54
0
1

Year Published

2006
2006
2021
2021

Publication Types

Select...
4
4

Relationship

2
6

Authors

Journals

citations
Cited by 55 publications
(57 citation statements)
references
References 51 publications
2
54
0
1
Order By: Relevance
“…While this cell death pathway is clearly dependent on caspase-1, it shows features of both apoptosis and necrosis (Haimovich & Venkatesan, 2006). Finally, S. flexneri can also induce a caspase-1-and IpaB-independent cell-death pathway, which is triggered by bacterial LPS (lipid A) delivered to the macrophage cytoplasm (Suzuki et al, 2005).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…While this cell death pathway is clearly dependent on caspase-1, it shows features of both apoptosis and necrosis (Haimovich & Venkatesan, 2006). Finally, S. flexneri can also induce a caspase-1-and IpaB-independent cell-death pathway, which is triggered by bacterial LPS (lipid A) delivered to the macrophage cytoplasm (Suzuki et al, 2005).…”
Section: Introductionmentioning
confidence: 99%
“…While this cell death pathway is clearly dependent on caspase-1, it shows features of both apoptosis and necrosis (Haimovich & Venkatesan, 2006). Finally, S. flexneri can also induce a caspase-1-and IpaB-independent cell-death pathway, which is triggered by bacterial LPS (lipid A) delivered to the macrophage cytoplasm (Suzuki et al, 2005).Here, we provide evidence that in S. flexneri-infected macrophages the translocator/effector protein IpaB is intracellularly secreted over a prolonged time, during which the bacterial pool is gradually depleted. To test the effect of CCCP (Sigma) on the growth of S. flexneri, the protonophore (25 mM) was added 2 h after inoculation, and 2.5 h later the bacteria were centrifuged and resuspended in TSB medium with or without 25 mM CCCP.…”
mentioning
confidence: 99%
“…Shigella multiply in the cytoplasm and induce cell death through activation of caspase-1 mediated by IpaB protein secreted via the type III secretion system, in turn leading to the maturation and release of IL-1␤ (5, 6). However, our recent work has shown that macrophages undergo proinflammatory necrotic cell death, and that the necrosis and caspase-1 activation are due to components common to Gram-negative bacteria (7). Another group has reported that Ipaf, a member of the pathogen-associated molecular pattern-sensing Nod family proteins, is implied a role in caspase-1 activation in Shigella-infected macrophages (8).…”
Section: High Vaccine Efficacy Against Shigellosis Of Recombinant Nonmentioning
confidence: 99%
“…Previous studies have shown that intracytosolic Shigella that have escaped from phagosomes induce death of the infected macrophages and dendritic cells (7,42), and that components common to Gram-negative bacteria induce necrotic cell death and caspase-1 activation (7). Mouse J774 macrophages were infected with wildtype Shigella, ⌬virG (conventional attenuated vaccine strain), ⌬ipaB, and ⌬ipaB/inv to determine whether ⌬ipaB/inv was capable of inducing cell death.…”
Section: Generation and Characterization Of An Invasin-expressing Shimentioning
confidence: 99%
“…Shigella invade resident macrophages in the lamina propria, and the bacteria escape from the phagosome into the cytosol. Infected macrophages undergo caspase-1-mediated cell death, termed pyroptosis, that is a newly identified pathway of programmed cell death associated with an inflammatory response, [12][13][14] but the precise mechanisms remain poorly understood.…”
Section: Introductionmentioning
confidence: 99%